Produção, caracterização e modelagem computacional dos aluminatos de bário - Rezende, Marcos Vinícius dos Santos (2011)
The defects and the optical properties of BaAl2O4 were carried out experimentally and compared with computer modelling predictions. In the computational modelling part, a set of potential parameters that could reproduce the available experimental crystal structures of all compounds of the family was obtained. Then the intrinsic and extrinsic defects were studied, including the process of reduction of rare earth ions. The solution energies of the extrinsic defects were obtained by two different methods. The first one is the infinite dilution approach, where a single defect is created in an infinite crystalline matrix. The second one, developed in our group, is the ideal solution approach that considers the total energetic coast to create a concentration of defects in the matrix. Using the previous results, the positions of the dopant and the first neighbours were used to calculate the crystal field parameters and the wavelength of the 4f internal transitions of the doping ions. A study of the equilibrium surfaces via computer modelling was also conducted, followed by prediction of the morphology of pure BaAl2O4. In the experimental part, the pure and doped BaAl2O4 samples were produced using the proteic sol-gel technique, where coconut water is used as a starting solvent for the metal salts. Thermal analysis techniques were employed to obtain the best conditions of calcination of the samples. The structural and microstructural characterization of the samples was made using the X-ray diffraction and transmission and scanning electron microscopy techniques. The analysis by X-ray diffraction showed the formation of BaAl2O4 phase calcined at 1100ºC/2hs and electronic microscopy showed nanoparticles with a hexagonal-like morphology with size varying from 50 to 100nm. The emission spectra of BaAl2O4: Eu exhibit typical transitions of Eu element indicating the incorporation of the dopant in the matrix of the produced material. Analysis of the results of X-ray spectroscopy (XAS) and emission of luminescence excited by X-ray samples (XEOL) enabled us to create a model that explains the behaviour found and can be used to propose a model for the scintillation properties of the doped nanopowders. The spectra showed typical emissions XEOL of doping ions (Eu, Dy and Ce). The dispersive X-ray absorption (DXAS) technique was used to monitor the kinetics of the reduction of Eu ions during irradiation using different reducing agents as provided by efficient computational modelling in order to verify the relationship between the generation of damage and the reduction process. A mechanism of XEOL for Eu-doped BaAl2O4 is proposed, taking into account the absorption of Xrays/ reduction of the Eu ions in the samples.